REVOLUTIONIZING CANCER TREATMENT: THE ROLE OF NANOTECHNOLOGY IN MODERN ONCOLOGY - Tyagi, Shaily; Kumar, Ashish; Chourasia, Anurag; Saini, Saket; Deeksha; Dixit, Anjali (International Journal of Research -GRANTHAALAYAH, 2023)
Cancer is one of the deadliest diseases of our time, affecting millions of people worldwide. Despite the significant progress made in cancer treatment over the past few decades, conventional cancer therapies such as chemotherapy, radiation, and surgery have their limitations, including toxicity, drug resistance, and damage to healthy cells and tissues. Therefore, researchers are constantly exploring new avenues for cancer treatment that are safer, more effective, and less invasive. One such avenue is the use of nanotechnology. Nanotechnology involves the manipulation and control of matter at the nanoscale, which is approximately one billionth of a meter. This technology has the potential to revolutionize cancer treatment by offering more targeted and precise therapy. Nanoparticles, for instance, can be engineered to target cancer cells specifically and deliver drugs or other therapeutic agents directly to them, minimizing damage to healthy cells. In this research, we aim to explore the current state of nanotechnology in modern oncology, its potential applications, and its limitations. We review the recent advancements in nanotechnology-based cancer therapy, including the development of targeted nanoparticles for drug delivery, imaging, and theranostics. One of the main advantages of using nanotechnology for cancer treatment is its ability to bypass the blood-brain barrier, allowing for the delivery of therapeutic agents to the brain. This opens up new avenues for the treatment of brain tumors, which are notoriously difficult to treat due to the barrier. Another potential application of nanotechnology in cancer treatment is the use of nanorobots that can be programmed to seek out and destroy cancer cells. These nanorobots can be designed to carry payloads of therapeutic agents or deliver hyperthermia to destroy cancer cells. Despite the many advantages of nanotechnology in cancer treatment, there are also challenges and limitations that need to be addressed. For instance, the toxicity and biocompatibility of nanoparticles need to be carefully evaluated to minimize potential harm to healthy cells and tissues. In conclusion, the role of nanotechnology in modern oncology has the potential to revolutionize cancer treatment. It offers more targeted and precise therapy, and can potentially overcome the limitations of conventional cancer therapies. However, further research is needed to fully explore the potential of nanotechnology in cancer treatment and to address the challenges and limitations associated with it.